Comparison of temperature lapse rates from the northern to the southern slopes of the Himalayas. (26th February 2015) - Kattel, Dambaru Ballab; Yao, Tandong; Yang, Wei; Gao, Yang; Tian, Lide
ABSTRACT: Based on 20‐year (1985–2004) records of surface‐air‐temperature at 16 stations between the elevations of 3553 m and 4801 m a.s.l. in the southeastern Tibetan Plateau (or the northern slopes of the eastern Himalayas), this paper examines the monthly, seasonal and annual characteristics of near‐surface temperature lapse rates (TLRs). A linear regression model was fitted for the lapse rate calculation. The annual cycle of the TLR shows a distinct seasonal pattern, i.e. steepest in winter and shallowest in summer. Results are partially consistent with those from the southern slopes of the central Himalayas, in particular in summer, and correspond to the warm, rainy and humid season. In response to the monsoonal effect, the released latent heat of water vapour condensation causes an increase in air temperature at higher elevations. Therefore, the TLR is shallowest in the summer. The considerable amount of solar radiation at higher elevations also causes a reduction of the TLR in this season. The lowest diurnal range of lapse rates for summer is associated with lower diurnal variability in net radiation due to cloud cover and relative humidity. The steepest TLR occurs in winter in association with intense cooling at higher elevations, corresponding to the continental dry and cold air surges, and considerable snow‐temperature feedback. Lower insolation, deeper snow cover and a weaker inversion effect cause a lower diurnal range of TLR in this season. The observed contrast of winter TLR from the northern to southern slopes of the Himalayas is due to differences in elevation and topography, as well as the pronounced effect of cold air surges.